Kajian Peran Konsistensi Diri Terhadap Prestasi Belajar Matematika - Leonard Leonard (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2013)
The aim of this research is to know the influence of self-consistency of the student toward the learning result (achievement) in junior high school 179 Jakarta. The research method which was used in the research is survey method. The population of research is all students in class VIII. Samples are taken by simple random sampling, consisted of 70 students. The research instrument is a self-consistency and mathematics learning achievement. Data analyzed by simple regression techniques. The hypothesis testing resulted in conclusion; there positive and significant effect of self-consistency toward mathematics learning achievement.